Determining the core vocabulary of Sepedi-speaking Grade R learners from the Sekhukhune district during regular school activities - Tonsing, Kerstin Monika (University of Pretoria, 2024)
Mini Dissertation (MA (Augmentative and Alternative Communication))--University of Pretoria, 2024.